Birth Weight in Different Etiologies of Disorders of Sex Development - GÜRAN, TÜLAY (ENDOCRINE SOC, 2017)
Context: It is well established that boys are heavier than girls at birth. Although the cause of birth weight (BW) difference is unknown, it has been proposed that it could be generated from prenatal androgen action. Objective: The aim of the current study was to determine the BW of children with disorders of sex development (DSD) of different etiologies and to evaluate the effects of androgen action on BW. Methods: Data regarding diagnosis, BW, gestational age, karyotype, and concomitant conditions were collected from the InternationalDisorders of SexDevelopment (I-DSD) Registry (www.i-dsd). BWstandard deviation score was calculated according to gestational age. Cases were evaluated according to disorder classification in I-DSD (i. e., disorders of gonadal development, androgen excess, androgen synthesis, androgen action, nonspecific disorder of undermasculinization groups, and Leydig cell defect). Results: A total of 533 cases were available; 400 (75%) cases were 46, XY, and 133 (25%) cases were 46, XX. Eighty cases (15%) were born small for gestational age (SGA). Frequency of SGA was higher in the 46, XY group (17.8%) than in the 46, XX (6.7%) group (P = 0.001). Mean BW standard deviation scores of cases with androgen excess and androgen deficiency [in disorders of gonadal development, androgen synthesis, and Leydig cell defect groups and androgen receptor gene (AR) mutation-positive cases in disorders of androgen action groups] were similar to normal childrenwith the same karyotype. SGA birth frequency was higher in the AR mutation-negative cases in disorders of androgen action group and in the nonspecific disorders of the undermasculinization group. Conclusions: BWdimorphism is unlikely to be explained by fetal androgen action per se. 46, XY DSDs due to nonspecific disorders of undermasculinizationare more frequently associatedwithfetal growth restriction, SGA, and concomitant conditions.
Keywords: ANDROGEN INSENSITIVITY SYNDROME; RECEPTOR GENE-MUTATIONS; FETAL-GROWTH; HEAD CIRCUMFERENCE; MATERNAL RISK; LENGTH; HYPOSPADIAS; DIMORPHISM; COHORT; BOYS